Approach-alcohol action tendencies can be inhibited by cognitive load - Sharbanee, Jason; Stritzke, W.; Jamalludin, M.; Wiers, R. (Springer, 2014)
Rationale: Dysregulated alcohol consumption has been attributed to an imbalance between an approach-alcohol action tendency and executive control processes. However, which specific executive control processes are involved is not known. One candidate executive process is interference suppression, which refers to the suppression of task-irrelevant information through the active maintenance of task-relevant information or a cognitive load. Objective: The present study aimed to (1) establish whether alcohol action tendency can be inhibited by interference suppression through the use of cognitive loads and (2) to assess whether individual differences in the degree of interference suppression from cognitive loads is related to individual differences in the ability to regulate alcohol consumption. Method: Two groups of social drinkers (total N = 58) who differed in their ability to regulate their alcohol consumption completed a novel cognitive load variant of the approach avoidance task (AAT) and an alcohol taste test. Results: Results indicated that (1) there was a relationship between alcohol bias on the AAT and alcohol consumption under low load, but not high load, consistent with the hypothesis that the action tendency would be inhibited through interference suppression, and (2) this effect of load was not modified by drinking group, with both groups demonstrating equivalent ability to inhibit the action tendency. Conclusions: The present findings suggest that alcohol action tendency can be inhibited through interference suppression, and that this is effective even for those that have difficulty regulating their alcohol consumption.